PELATIHAN PERAWATAN DAN PERBAIKAN PERALATAN LISTRIK RUMAH TANGGA BAGI MASYARAKAT RUKUN WARGA 09 KELURAHAN BUNULREJO – KOTA MALANG - Heri Sungkowo; Mochammad Mieftah; Slamet Nurhadi; Epiwardi; Sukamdi (UPT Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Malang, 2020)
Maintenance and repair of household electrical appliances for the Rukun community Residents 09 Bunulrejo Village / Kec. Blimbing - Malang City, gives additional the skills and motivation for the Rukun Community of 09 Bunulrejo Village for practice maintenance and repair of household electrical appliances for the Rukun community Residents 09 Bunulrejo Village. Besides that it can also improve skills addition to the community of Rukun Warga 09 Kelurahan Bunulrejo in the field of care and repair of household electrical appliances for the 09 Rukun Warga community in the Village Bunulrejo that applies in this era.